PENGARUH PEMBERIAN OCIMUM BASILICUM ( DAUN KEMANGI ) TERHADAP KEJADIAN KEPUTIHAN PATOLOGIS PADA WANITA USIA SUBUR DI PUSKESMAS KRAKSAAN KABUPATEN PROBOLINGGO: The Effect Of Ocimum Bacilicum (Kemangi Leaves) To Cure Leucorrhoeain Childbearing Age Women, In Kraksaan Community Health Center Kraksaan District Probolinggo - Fifin Azizah Zainal Arifin (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
Approximately 90% of Indonesian women have the potential to experience leucorrhoea. The results of research in East Java in 2013 showed from 855,281 women, 45% of them experiencedleucorrhoea. Leucorrhoeadata in Probolinggoshowed 1.91% by 2014. Untreated leucorrhoea can cause pelvic inflammatory disease and may cause infertility. One of non pharmacological therapy is using kemangi leaves. Kemangileaves have eugenolwhich contains substances that can kill the cause of leucorrhoea. The purpose of this research is to analyze the effect of ocimumbacilicum(kemangi leaves) to cure leucorrhoea in childbearing age women in Kraksaan Community Health Center Kraksaan District Probolinggo2017. Research design was pre experimental with one group pretest posttest. The population was all women of childbearing age who experiencedleucorrhoea as many as 34 people and sample was 15 people which taken by using accidental sampling. Data were collected by using observation sheets and interview sheets. After it had been processed then tested by using McNemar Test. The results showed that before they were given the leaves, all respondents (100%) experienced leucorrhoea and after given, the majority of respondents (73%) experienced physiological fluoralbus. The result of statistical test was known ? value = 0,001 <? = 0,05, so H0 was rejected. It means there was an effect of ocimumbacilicum (kemangi leaves) to cure leucorrhoea in childbearing age women in Kraksaan Community Health Center Kraksaan District Probolinggo2017. Educational institution can use this research result as a reference about the utilization of traditional medicine especially by using kemangi leaves to reduce leucorrhoea patologist. Respondents can take advantage of kemangi leaves to reduce leucorrhoea and should increase independent efforts to reduce leucorrhoea, such as maintaining the hygiene of feminine areas.